Traditional serrated adenoma of the sigmoid colon with osseous metaplasia: a case report - Montalvo, Nelson F (BioMed Central, 2012)
INTRODUCTION: Osseous metaplasia in the gastrointestinal tract is a rare phenomenon. CASE PRESENTATION: We present the case of a 62-year-old Hispanic man with two colonic polypoid lesions, one of which, upon resection and histopathological examination, was found to be a traditional serrated adenoma with a focus of stromal osseous metaplasia. CONCLUSIONS: Our patient’s case is the third report of stromal osseous metaplasia in a traditional serrated adenoma of the sigmoid colon.